2012
DOI: 10.3390/medicina48100076
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Randomized Controlled Study on Decompressive Craniectomy in Treatment of Malignant Middle Cerebral Artery Stroke

Abstract: Background and Objective. Studies on decompressive craniectomy (DCE) after a malignant middle cerebral artery (MCA) stroke in selected population show an increased probability of survival without increasing the number of very severely disabled. Cerebral infarct volume (CIV) as a triage criterion for performing surgery has not been discussed in literature. The aim of this study was to investigate the value of CIV and initial National Institutes of Health Stroke Scale (NIHHS) and Glasgow Coma Scale (GCS) scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 13 publications
(39 reference statements)
0
61
0
3
Order By: Relevance
“…26 Inclusion criteria for the individual trials were similar, with exception of the prespecified age ranges (table). Baseline patient characteristics of the treatment groups were well-matched with exception of Jüttler et al 25 and Slezins et al, 23 which reported higher mean NIH Stroke Scale scores in the medically managed group. Slezins et al 23 also reported a lower mean age in the patients undergoing DC.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 93%
See 4 more Smart Citations
“…26 Inclusion criteria for the individual trials were similar, with exception of the prespecified age ranges (table). Baseline patient characteristics of the treatment groups were well-matched with exception of Jüttler et al 25 and Slezins et al, 23 which reported higher mean NIH Stroke Scale scores in the medically managed group. Slezins et al 23 also reported a lower mean age in the patients undergoing DC.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 93%
“…Hofmeijer et al 5 reported a post hoc analysis of 39 patients enrolled in HAMLET within 48 hours of stroke onset, but did not report baseline patient characteristics or whether their initial randomization stratification was maintained in this subgroup. 5,27 Secondary to these concerns, Slezins et al 23 and Hofmeijer et al 5 both received an unclear risk of bias rating. A full risk of bias rating table is included in figure e-1.…”
Section: Risk Of Bias For Independent Studiesmentioning
confidence: 99%
See 3 more Smart Citations